(untitled) (Vietnam Journal of Community Medicine, 2022)
Objective: Description of nutritional status of outpatients with type 2 diabetes treated in Quang Ninh General Hospital in 2020-2021. Method: A cross-sectional description was carried out on 457 outpatients with type 2 diabetes. Results: The majority (61.1%) of the study subjects were overweight (30.6%) and obese (30.5%); The prevalence of overweight in men (36.0%) was higher than that of women (24.0%), while the rate of obesity in women (33.4%) was higher than that of men (28.1%). CED rate was only 1.3%. Prevalence of subjects with high waist circumference (male ≥90 cm, female ≥ 80 cm) was 50.1%; The percentage of women with high waist circumference (75.5%) was higher than that of men (29.6%). The majority of subjects had a normal VE/VM ratio, accounting for 67.6%; 32.4% of subjects had high VE/VM ratio. In which, the high VE/VM ratio in women accounted for a higher rate of 70.6% while the high VE/VM ratio in men accounts for only 1.6%.